The Role of αvβ3 Integrins in Vascular Healing - Sajid, Mansoor; Stouffer, George A. (Thrombosis and Haemostasis, 2002)
αvβ3 integrins play an important role in vascular healing. Vascular injury is a stimulus for expression of αvβ3 by vascular cells and, among other effects, αvβ3 integrins function in the adhesion of activated platelets to endothelium, white cell/endothelium interactions, plateletmediated thrombin generation, fibrin clot retraction by nucleated cells, smooth muscle cell (SMC) migration and proliferation, vascular cell apoptosis, and vascular remodeling. There are ten different animal models in which treatment with αvβ3 antagonists reduced the vascular response, including (neo)intima formation, after mechanical injury. These studies, along with mechanistic data derived from cell culture studies, provide compelling evidence that αvβ3 integrins are involved in vascular repair processes. The challenge is to develop a therapeutic agent that will prove effective in reducing restenosis in humans following percutaneous coronary intervention (PCI).
Keywords: Victronectin receptor; angioplasty; vascular smooth muscle